Study of the disaster-causing mechanism and reinforcement measures for soft rock deformation and lining cracking - Shi, J. W.; Zhou, P. Y.; Li, X.; Fan, S. Y.; Zhou, Z. F.; Zhi, B.; Cheng, Y. (Frontiers in Earth Science, 2023)
Underground engineering construction is facing increasingly complex geological conditions and engineering challenges, such as surrounding rock deformation and lining cracking, that seriously threaten the safety of tunnel construction and operation. Aiming at these problems, a pipeline tunnel crossing jointed expansive mudstone strata was taken as an example, and the disaster characteristics of surrounding rock and lining were analyzed through field investigation. The disaster-causing mechanism and corresponding control measures were studied through laboratory tests and numerical simulations, which were then applied to actual construction. Meanwhile, the deformation and stress response of the surrounding rock and tunnel structure were analyzed and investigated through monitoring and numerical data. The results showed that the vault settlement and horizontal convergence deformation of surrounding rock were reduced by 64.69 mm and 54.74 mm, respectively, under the improved construction scheme. The maximum surrounding rock stress was 430.26 kPa under the improved construction scheme, which was 18.15% lower than the original stress. The maximum axial force of the steel arch frame was 33.02 kN, ensuring the stability of the supporting structure and tunnel construction safety. Finally, the rationality and effectiveness of the reinforcement measures adopted were assessed.